1995
DOI: 10.1620/tjem.176.137
|View full text |Cite
|
Sign up to set email alerts
|

A Radioimmunometric Assay for Urinary .ALPHA.2-Macroglobulin.

Abstract: Assay for Urinary a2-Macroglobulin. Tohoku J. Exp. Med., 1995, 176 (3), [137][138][139][140][141][142][143][144][145][146][147] To measure urinary a2-macroglobulin levels, a sensitive radioimmunometric assay was established. The least detectable level of this assay was 225 pg/ml. A linear correlation between a2-macroglobulin levels and serial dilution of urine samples was found. Western blot analysis and study on column chromatography revealed that the molecular weight of a2-macroglobulin in urine was identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Urinary and serum IgG, IgG4, CRL [16], and A2 [17]were measured by immunoradiometric assay. In brief, 0.3 ml of coating antiserum was added to the assay tubes (Nunc), and the reaction was allowed to proceed at room temperature for 24 h. The tubes were washed three times with 0.4 ml of 0.1  M phosphate buffer (pH 7.4) containing 0.05% Tween 20, 0.3% bovine serum Alb, and 0.01% NaN 3 (washing buffer) and incubated with 0.4 ml of washing buffer overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary and serum IgG, IgG4, CRL [16], and A2 [17]were measured by immunoradiometric assay. In brief, 0.3 ml of coating antiserum was added to the assay tubes (Nunc), and the reaction was allowed to proceed at room temperature for 24 h. The tubes were washed three times with 0.4 ml of 0.1  M phosphate buffer (pH 7.4) containing 0.05% Tween 20, 0.3% bovine serum Alb, and 0.01% NaN 3 (washing buffer) and incubated with 0.4 ml of washing buffer overnight.…”
Section: Methodsmentioning
confidence: 99%
“…To answer these questions, urinary excretions of various plasma proteins with various molecular radii and isoelectric points (pIs), namely albumin (Alb), IgG, IgG4, ceruloplasmin (CRL) [16], and α 2 -macroglobulin (A2) [17], were measured in healthy subjects after ingestion of a beef meal or of a tuna fish meal.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the proteins identified have been previously described as potential biomarkers of glomerulopathies, such as a 2 -macroglobulin (a 2 -M) and alpha-1anti-trypsin (AAT). a 2 -M, a 720-kDa glycoprotein mainly synthesized in the liver, was demonstrated to be increased in plasma and urine of patients with nephrotic syndrome regardless of the primary disease, and was suggested to be a marker of glomerular diseases [18][19][20][21]. Thus, in a study investigating 199 patients with renal biopsy-proven glomerulopathies, Tencer et al [20] suggested that the urinary a 2 -M selectivity index could be used to effectively distinguish two types of glomerular disorders (minimal change nephropathy and crescentic necrotizing glomerulonephritis) from all the other analyzed glomerular diseases.…”
Section: Proteomic Analysis Of the Podocytes Vesicle-enriched Urinarymentioning
confidence: 99%
“…Concentrations of IgG, ceruloplasmin, and ␣ 2 -macroglobulin of serum and urine samples were measured by immunoradiometric assay according to procedures previously reported (4,9,12,18). Intraand interassay coefficient variances for the assays of these plasma proteins were almost 3 and 10%, respectively.…”
Section: Laboratory Proceduresmentioning
confidence: 99%